GIVING REWARD HAVE GREAT IMPACT ON JOBSATISFACTION AND TEACHER COMMITMENT AT SMA SATYA DHARMA BALUNG JEMBER - Iit Maulidah; Imam Suroso; Zainollah Zainollah (MBA : Journal of Management and Business Aplication, 2019)
The  title  of  this  research  article  is  "giving reward  has  great  impact onjobsatisfaction  and teacher commitmentat SMA Satya Dharma Balung Jember". This study aims to analyze and examine  the  effect  of  intrinsic  rewards  and  extrinsic  rewards  on  job  satisfaction  and  teacher commitment   in   SMA   Satya   Dharma   Balung Jember.   This   research   includes   causal, quantitative  research,  because  this  study  intends  to  explain  causal  relationships  (causality) between   variables   through   hypothesis   testing   that   has   been   formulated.   The   research population  is  all  high  school  teachers  of  Satya  Dharma  Balung  Jember.  The  sampling technique used is Proportional Stratified Random Sampling. The hypothesis proposed in this study  is  that  there  is  a  direct,  positive,  and  significant  influence  of  intrinsic  rewards,  and extrinsic rewards to job satisfaction and teachers commitment of SMA Satya Dharma Balung Jember. The  test  validity  of  research  instrument  used construct  validity.  Reliability  test was done with Cronbach Alpha. The method of analysis used is path analysis and the calculation process  is  approached  with  multiple  linear  regression  analysis.  The  results  showed  that intrinsic  rewards  and  extrinsic  rewards  had  a  direct,  positive,  and  significant  impact  on theteacher's job satisfactionofSatya Dharma Balung Jember high school. Intrinsic rewards, and extrinsic  rewards hada  direct,  positive,  and  significant  impact  on  the  work  commitment  of SMA Satya Dharma Balung Jember teachers.  Intrinsic rewards and extrinsic rewards hadan indirect,  positive,  and  significant  impact  on  teacher  commitment,  through  job  satisfaction. Based on the findings of this study, it is expected that the award received in accordance with what  is  perceived,  so  that  it  appears on  job  satisfaction  and  ultimately  lead  to  work commitments.